A Kinetic Study for Malachite Green Removal of Adsorption over Multiwall Carbon Nanotubes - Kahdum, Bashaer J (Iraqi Journal of Science, 2021)
Current study was carried out to determine the adsorption ability of the Multiwall carbon nanotubes (MWCNTs) by adsorption Malachite Green dye from an aqueous solution. Crystal structure of the materials was measured using powder X-rays diffraction (PXRD), UV–Vis diffuse reflectance and specific surface area (BET). Many parameters that affecting the adsorption process such as contact time, pH, adsorbent dosage, initial dye concentration and temperature were studied. The outcome showed that an increasing occurred in the adsorbent dosage and the rate of dye removal, and the best efficiency for Malachite Green dye removal was amounted 99. 11 %. The results were obtained at optimal reaction conditions were pH = 5.5, catalyst weight 0.15 g, T = 298 K and reaction time = 1 h. In addition, the equilibrium adsorption isotherms and kinetics studies were investigated using Freundlich and Langmuir isotherms. The Freundlich isotherm (R2=0.9506) was found to be the best fitted for experimental data of this study .A higher correlation value of kinetic model was observed close to pseudo-second-order (R2=0.999) compared to other kinetic models.